Developing a beach erosion sensitivity indicator using relational spatial databases and Analytic Hierarchy Process - Díaz-Cuevas, Pilar; Prieto-Campos, Antonio; Ojeda-Zújar, José (Ocean & coastal management, 2020)
This paper presents a methodology that is based on the use of relational spatial databases and Analytic Hierarchy Process (AHP), to generate an indicator of sensitivity to erosive processes for dry beaches, which was then applied in the province of Cádiz (Southern Spain). The variables ‘width of dry beach’; ‘accommodation space – width and type of sedimentary substrate’; and ‘mid-term erosion rate’ (1977–2013) are calculated in detail (1:2500). Following this, the accommodation space variable is weighted according to its sedimentary substrate before calculating the sensitivity indicator by aggregating all variables. Results suggest that Mediterranean beaches are more likely to be erosion sensitive than Atlantic ones. Both groups share similar features: similar dry beach width, a tendency to erode, and the existence of little or no accommodation space. Of those beaches in the extremely sensitive bracket, 29% are located in urban areas, especially common along the Mediterranean facade, where the presence of infrastructure (mainly retaining walls and seaside promenades) prevents both the increase of the beach's potential expansion areas and the oscillation of the shoreline. The methodology developed can be applied to other regions and will be of interest for coastal planners and managers, whom can use this information to understand coastal erosion hazards and to readily identify areas that are less resilient to erosive phenomena and where more detailed analyses should be carried out. •A simple beach erosion sensitive indicator is developed an applied in Cadiz (south of Spain).•Mediterranean beaches are more likely to be erosion sensitive than Atlantic ones.•Results are validated by comparing with regenerated beaches.•The indicator points out zones where more detailed analysis is desirable optimising time and resources.•The indicator can be applied to other regions and is useful for coastal planners.